PKI and BTI’s Strategy for Gaining Farmers' Sympathy Through Land Reform (1960–1963) - Rakhmanto, Bambang (Universitas Negeri Semarang, 2024)
This study aims to examine the role of the Indonesian Communist Party (PKI) and the Indonesian Farmers' Front (BTI) in garnering farmers' sympathy by assisting them in gaining access to land. Their efforts were carried out through the implementation of the government’s land reform policy. In this study, the author collected and organized data through library research, including archives, books, journals, newspapers, articles, and relevant websites. Land, as the primary source of livelihood for the majority of the population working as farmers. Despite achieving independence for 15 years, most Indonesian farmers in 1960–1963 still faced challenges in accessing land. Data indicate that 60% of farmers were landless, while large-scale land ownership remained concentrated in the hands of a small elite. The Indonesian government sought to address this inequality through land reform policies established under the Basic Agrarian Law (UUPA) of 1960. The findings of this study reveal that the PKI and BTI actively advocated for agrarian reform and fought for the rights of poor farmers.